Perception of Post graduate educational environment among Radiology Residents Using PHEEM criteria: A comparison between two public sector hospitals - Sara Nisar, Tanvir Khaliq (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Educational environment includes the support system of physical surrounding, equipment and human resource that helps to motivate engagement towards acquiring knowledge and learning. Assessment of student’s perception on educational environment provides opportunities for improving learning experiences. Aim: To compare the perception of the learning environment at two public sector tertiary care hospitals in different cities of Pakistan using a standardized validated tool, PHEEM. Methodology: In this cross sectional study, using 40 statement PHEEM Validated questionnaire, radiology residents of FCPS, MCPS, FRCR and MD working at two public sector teaching hospitals were included. The study was conducted in months of August and September 2021 with non-purposive convenience sampling technique. The individual perception scores by residents were calculated. The means, standard deviation and standard error of mean were calculated for individual domains as well as global scores and then compared in the two different hospitals, different levels in years of residency and both genders. A p-value of ≤0.05 was taken as significant. Results: There were 45 radiology residents in total, who completed the questionnaire. The trainees perceived educational environment positive at their institutes, with a global mean of 73.3 (SD: 28.5). Autonomy, teaching and social support were rated 25.2 (SD 9.2), 30.1 (SD 13.4) and 18.1 (SD 7.6) respectively. Gender wise there was no difference between the PHEEM scores of the two groups. P value was 0.4. Similarly year of training did not have much difference either with a p value of 0.9 in the total PHEEM score of 1st year and 4th year residents. Conclusion: Our results show that we have plenty of problems in both the hospitals which need to be addressed one by one. Keywords: educational environment, PHEEM, standardized, perception